Treatment of CD30-positive systemic mastocytosis with brentuximab vedotin. (May 2016) - Borate, Uma; Mehta, Amitkumar; Reddy, Vishnu; Tsai, Michaela; Josephson, Neil; Schnadig, Ian
Highlights: Cytoreductive therapies in SM are limited by response degree/length and toxicities. 4 patients with SM were treated with the anti-CD30 ADC brentuximab vedotin. 2 of 4 patients achieved a clinical response to brentuximab vedotin. Brentuximab vedotin was well-tolerated with side effects managed by dose adjustment. Abstract: Systemic mastocytosis is a myeloproliferative neoplasm with varying presentation that is caused by infiltration of neoplastic mast cells into extracutaneous tissues. Cytoreductive therapy is used to control organ dysfunction in aggressive systemic mastocytosis and is sometimes needed for control of severe refractory symptoms in patients with indolent disease. However, current standard cytoreductive agents are limited by their suboptimal degree and duration of response and associated significant toxicities, highlighting the need for novel treatments for systemic mastocytosis. Recent studies have identified CD30 as a therapeutic target in systemic mastocytosis, as CD30 is expressed on a majority of neoplastic mast cells. In this case series, the clinical outcomes of 4 patients with aggressive or indolent systemic mastocytosis treated with the anti-CD30 antibody‐drug conjugate brentuximab vedotin are reported. Two patients showed evidence of a response to treatment with a reduction in disease burden, 1 of which has demonstrated a durable response with ongoing benefit for more than 3 years. Treatment with brentuximab vedotin was well-tolerated with side effects that were effectively managed by dose modifications. The results presented suggest that brentuximab vedotin is active in systemic mastocytosis and can induce durable responses with a manageable toxicity profile.